Pengaruh Keaktifan Siswa dalam Kegiatan Ekstrakurikuler Kejuruan dan Motivasi Belajar terhadap Hasil Belajar - Ria Sartika Juniarti; Rahmatul Irfan (Journal of Information Technology and Education (JITED), 2024)
The objectives of the study: (1) Analyze whether there is an Influence of Student Activeness in Vocational Extracurricular Activities and Learning Motivation on Learning Outcomes in Printing Graphic Design Subjects in class XI SMKN 7 Yogyakarta (2) Analyze whether there is an Influence of Student Activity in Vocational Extracurricular Activities on Learning Outcomes in Printing Graphic Design Subjects in class XI SMKN 7 Yogyakarta (3) Analyze whether there is an Influence of Learning Motivation on Learning Outcomes in Printing Graphic Design Subjects in class XI SMKN 7 Yogyakarta. This research is an ex post facto research with a quantitative approach. The results of this study show that: (1) There is a significant influence between student activeness in vocational extracurricular activities and learning motivation affects learning outcomes. This is shown from the results of simultaneous tests by obtaining significance values of 0.00 < 0.05; (2) There is a significant influence between student activity in vocational extracurricular activities on learning outcomes with a significance value of 0.00 < 0.05; (3) There is a significant influence between learning motivation on learning outcomes with a significance value of 0.00 < 0.05 learning in the subject of Graphic Design Printing class XI at SMKN 7 Yogyakarta for the 2022/2023 academic year.